The Prince of Darkness : Radical Evil and the Power of Good in History. - Russell, Jeffrey Burton (Cornell University Press, 2016)
The Devil, Satan, Lucifer, Mephistopheles - throughout history the Prince of Darkness, the Western world's most powerful symbol of evil, has taken many names and shapes. Jeffrey Burton Russell here chronicles the remarkable story of the Devil from antiquity to the present. While recounting how past generations have personified evil, he deepens our understanding of the ways in which people have dealt with the enduring problem of radical evil. After a compelling essay on the nature of evil, Russell uncovers the origins of the concept of the Devil in various early cultures and then traces its evolution in Western thought from the time of the ancient Hebrews through the first centuries of the Christian era. Next he turns to the medieval view of the Devil, focusing on images found in folklore, scholastic thought, art, literature, mysticism, and witchcraft. Finally, he follows the Devil into our own era, where he draws on examples from theology, philosophy, art, literature, and popular culture to describe the great changes in this traditional notion of evil brought about by the intellectual and cultural developments of modern times. Is the Devil an outmoded superstition, as most educated people today believe? Or do the horrors of the twentieth century and the specter of nuclear war make all too clear the continuing need for some vital symbol of radical evil? A single-volume distillation of Russell's epic tetralogy on the nature and personification of evil from ancient times to the present (published by Cornell University Press between 1977 and 1986), The Prince of Darkness invites readers to confront these and other critical questions as they explore the past faces of that figure who has been called the second most famous personage in Christianity.